Wideband and high-gain patch antenna with reflective focusing metasurface - Zhou, Enyu; Cheng, Yongzhi; Chen, Fu; Luo, Hui (International journal of electronics and communications, 2021)
In this paper, a high-gain and wideband circular polarization (CP) patch antenna using reflective focusing metasurface was proposed and demonstrated. The initial design of patch antenna is made of a slot planar patch radiation part fed by coplanar waveguide (CPW). The simulated return loss below −10 dB of the initial design is from 6.2 to 13.8 GHz with the relative bandwidth of 76%, and the average gain is only about 4.5 dBi. In addition, the simulated 3-dB axial ratio bandwidth (ARBW) of the initial design is 78.7% from 6 to 13.8 GHz. The antenna structure was modified to enhance the gain and radiation performance by adding the reflective focusing geometric metasurface. The metasurface with wideband high efficiency cross-polarization reflection, is arranged to construct the phase gradient paraboloid for energy gathering. Simulation results indicated that the antenna combined with reflective focusing metasurface achieves an effective wideband impedance bandwidth (return loss < −10 dB) of 57.9% from 6 to 10.9 GHz and 11.98% from 12.24 to 13.8 GHz. The simulated average gain coefficient is over 6.5 dBi and the gain peak is up to 12.6 dBi at 11 GHz. In addition, the simulated 3-dB ARBW of the modified antenna are 18.2% from 6.5 to 7.8 GHz, 36.8% from 8.2 to 11.9 GHz and 9.3% from 12.3 to 13.5 GHz, respectively. This work shows a huge potential in wideband high speed data system, and provides an efficient method for gain enhancement in antenna design.